Spinal Cord Compression: An Infrequent Complication of SAPHO Syndrome - Sonia REKİK,; Maroua SLOUMA,; Hela SAHLİ,; Elhem CHEOUR,; Mohamed ELLEUCH, (Archives of Rheumatology, 2015)
Synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome is a spectrum of inflammatory disorders including mainly rheumatologic and dermatological symptoms. In this article, we report a 50-year-old male patient of SAPHO revealed by spondylodiscitis, complicated by severe destruction, and kyphotic deformity leading to paralysis. Diagnosis was based on the association of sternoclavicular pain, palmar and plantar pustulosis, and radiological signs of inflammatory spondylodiscitis and vertebral osteitis. Computed tomography-guided discovertebral biopsy demonstrated nonspecific inflammation and culture of the specimen was negative. Nonsteroidal antiinflammatory drug treatment was initiated. One year later, the patient presented with spinal cord compression. The paralysis improved by surgery, and the patient recovered motor functions. The occurrence of spinal cord compression in SAPHO syndrome is rare. To our knowledge, less than eight cases of neurological deficit related to SAPHO syndrome have been reported in the literature. We also emphasize the effect of biological treatment in SAPHO syndrome.